The synergic interaction between environmental factors (pH and NaCl) and the physiological state (vegetative cells and spores) provides new possibilities for optimizing processes to manage risk of C. sporogenes spoilage. (December 2021) - Boix, Emmanuelle; Couvert, Olivier; André, Stéphane; Coroller, Louis
Abstract: Clostridium sporogenes has been widely used as a surrogate for proteolytic C. botulinum for validating thermal processes in low-acid cans. To limit the intensity of heat treatments, industrials must use other ways of control as an association of acidic and saline environment after a low heat treatment. The probability of growth of pH (7–4.4), sodium chloride concentration (0–11%) and heat treatment (80°C-10 min; 100°C-1.5 min and 5.2 min) were studied on C. sporogenes PA 3679 spores and vegetative cells. Vegetative cells or heat-treated spores were inoculated in PYGm broth at 30 °C for 48 days in anaerobic conditions. Vegetative cells growth (pH 4.6–pH 4.5; 7%–8% NaCl) range is larger than the spore one (pH 5.2–pH 5.0; 6%–7% NaCl). Spores germination and outgrowth rage is decreased if the spores are heat-treated at 100 °C for 1.5 min (pH 5.5–5.3; 4%–5% NaCl) and 5.2 min (pH 5.7–5.3; 4%–5% NaCl). The C. sporogenes PA 3679 spores germination and outgrowth is impacted by their physiological state. The synergic interaction between environmental factors (pH and NaCl) and the physiological state (vegetative cells and spores) opening new possibilities for optimizing food formulation processes to manage the risks of C. sporogenes spoilage. Highlights: Vegetative cells and spores have not the same pH growth limits for the parameters analysed. If the intensity of heat treatment increases, the spore growth range is decreases. Physiological state impacts the growth limits of C. sporogenes PA 3679. The combination of water activity, pH and heat treatment prevent the spore growth.